LIVED EXPERIENCE OF HIGH SCHOOL TEACHERS AMIDST COVID-19 PANDEMIC: A PHENOMENOLOGICAL STUDY - Michelle Sarah Kainama; Anne Lou Hendriks (IKIP Siliwangi, 2021)
The purpose of this research was to discover the experiences of English teachers in Jayapura, Papua in terms of the execution of online learning during the COVID-19 pandemic. A qualitative method was used to find out the target needs related to teachers’ experiences. The data collection used was semi-structured interviews with five English teachers selected as the participants in this research. This research found English teachers experiences out regarding online classes that have been made in the outspread of COVID-19. The major results of this study showed there are several areas on teachers’ experiences in performing online classes; interaction that is both high-quality and timely, technical issues, and the participation of the students.